Comparison of Whole-Body Ga-68 DOTA TATE Positron Emission Tomography and Magnetic Resonance Imaging in the Detection of Bone Metastasis of Neuroendocrine Tumor in Simultaneous 3T Positron Emission Tomography/Computed Tomography - Asa, Sertaç; Kibar, Ali; Uslu-Beşli, Lebriz; Eryürekli, Ali Ergün; Samancı, Cesur; Sağer, Sait; Sönmezoğlu, Kerim (Cerrahpaşa Medical Journal, 2022)
Objective: Neuroendocrine tumors are rare neoplasms that often arise from neuroendocrine cells in gastr o-ent ero-p ancre atic and bronchopulmonary tissues. Bone metastases are observed less frequently than liver metastases. In current oncological practice, Ga-68 DOTA-labeled peptide positron emission tomography/computed tomography is performed in neuroendocrine tumor patients. Thanks to positron emission tomography/magnetic resonance imaging devices developed in recent years, it has become possible to obtain positron emission tomography images and magnetic resonance imaging sequences. This study aimed to compare the diagnostic efficiency between Ga-68 DOTA TATE positron emission tomography and magnetic resonance imaging components in detecting bone metastases in patients with neuroendocrine tumor undergoing Ga-68 DOTA TATE positron emission tomography/magnetic resonance imaging. Methods: This study included 63 patients with neuroendocrine tumor who underwent Ga-68 DOTA TATE positron emission tomography/magnetic resonance imaging screening. First, positron emission tomography images and magnetic resonance imaging sequences were evaluated separately to detect bone metastases. Afterward, both the components were assessed together, and their contribution was investigated according to positron emission tomography images alone. Results: Patient-based sensitivity, specificity, positive predictive value, negative predictive value, and accuracy analysis for bone metastasis were 0.96, 0.87, 0.82, 0.97, and 0.90 for positron emission tomography and 0.71, 0.87, 0.77, 0.82, and 0.80 for magnetic resonance imaging, respectively. Diffusion-weighted imaging and short-tau inversion recovery sequences do not seem to provide any additional benefit to the clinical approach. Conclusion: Ga-68 DOTA TATE positron emission tomography/magnetic resonance imaging evaluated bone lesions in neuroendocrine tumor patients with high sensitivity but low specificity. Our study shows that diffusion-weighted imaging and short-tau inversion recovery sequences do not contribute to the clinical approach and lead to ambiguous results. It is thought that removing these sequences from the protocol will increase patient compliance, and prospective studies involving large patient groups are needed. Cite this article as: Asa S, Kibar A, Uslu-Besli L, et al. Comparison of whole-body Ga-68 DOTATATE positron emission tomography and magnetic resonance imaging in the detection of bone metastasis of neuroendocrine tumor in simultaneous 3T positron emission tomography/computed tomography. Cerrahpasa Med J. 2023;47(1):7-13.